Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202180073592.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-10-21
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-10-21
AI Technical Summary
The high Co content in lithium transition metal composite oxides leads to high costs and reduced cycle characteristics. Existing technologies struggle to maintain battery stability and cycle performance while reducing Co content.
A lithium transition metal composite oxide containing Ni, Mn and Al is used, with the Co content limited to below 1.5 atomic%, and a non-aqueous electrolyte containing fluorosulfonate is used in combination with isocyanurate to form a stable coating to inhibit metal dissolution and increase internal resistance.
While reducing the Co content, the excellent cycle characteristics of the non-aqueous electrolyte secondary battery are ensured and the increase in internal resistance is suppressed, thereby improving the stability and capacity of the battery.
Smart Images

Figure CN116508175B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to non-aqueous electrolyte secondary batteries. Background Technology
[0002] Non-aqueous electrolyte secondary batteries, represented by lithium-ion batteries, have a positive electrode, a negative electrode, and a non-aqueous electrolyte. To ensure the superior characteristics of non-aqueous electrolyte secondary batteries, attempts are being made to improve their structural components.
[0003] Patent Document 1 proposes a non-aqueous electrolyte containing: a compound (A) having an organic group with 1 to 20 carbon atoms that can have substituents on the nitrogen atom of isocyanuric acid, a nitrile compound, an isocyanuric acid ester compound, a difluorophosphate compound, or a fluorosulfonate, etc.
[0004] Patent document 2 proposes a positive electrode active material for non-aqueous electrolyte secondary batteries, which is derived from formula 1: Li x Ni 1-y-z-v-w Co y Al z M 1 v M 2 w The lithium-containing composite oxide shown in O2, with element M in Formula 1 1 To select at least one element from the group consisting of Mn, Ti, Y, Nb, Mo, and W, element M... 2 It is to select at least two elements from the group consisting of Mg, Ca, Sr, and Ba, and element M 2 It contains at least Mg and Ca, and Equation 1 satisfies 0.97≤x≤1.1, 0.05≤y≤0.35, 0.005≤z≤0.1, 0.0001≤v≤0.05 and 0.0001≤w≤0.05. The primary particles of the composite oxide are aggregated to form secondary particles. The average particle size of the primary particles of the composite oxide is greater than 0.1μm and less than 3μm, and the average particle size of the secondary particles of the composite oxide is greater than 8μm and less than 20μm.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-194930
[0008] Patent Document 2: Japanese Patent Application Publication No. 2006-310181 Summary of the Invention
[0009] The problem the invention aims to solve
[0010] The price of Co in lithium transition metal composite oxides has surged in recent years. Reducing the Co content in lithium transition metal composite oxides is cost-effective, but it degrades the cycle characteristics of non-aqueous electrolyte secondary batteries. This is believed to be due to the instability of the crystal structure of lithium transition metal composite oxides, which promotes degradation through side reactions.
[0011] Solution for solving the problem
[0012] One aspect of this disclosure relates to a non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a positive electrode active material, which comprises a lithium transition metal composite oxide containing Ni, Mn, and Al. The proportions of Ni, Mn, and Al in the lithium transition metal composite oxide, excluding Li, are respectively: Ni 50 atomic% or more, Mn 10 atomic% or less, and Al 10 atomic% or less. If the lithium transition metal composite oxide contains Co, the proportion of Co in the lithium transition metal composite oxide, excluding Li, is 1.5 atomic% or less. The non-aqueous electrolyte comprises a fluorosulfonate.
[0013] The effects of the invention
[0014] Even when using lithium transition metal composite oxides without Co or with low Co content, it is possible to provide non-aqueous electrolyte secondary batteries with excellent cycle characteristics.
[0015] The novel features of the invention are described in the appended claims, but the composition and content of this disclosure can be further understood by referring to other objects and features of the invention and by the following detailed description with reference to the accompanying drawings. Attached Figure Description
[0016] Figure 1 This is a schematic perspective view obtained by cutting out a portion of a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure. Detailed Implementation
[0017] As a non-aqueous electrolyte secondary battery disclosed herein, it comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode contains a positive electrode active material. The positive electrode active material contains a lithium transition metal composite oxide containing Ni, Mn, and Al.
[0018] If the Co content of the lithium-containing composite oxide can be reduced and the Ni content increased, it is cost-effective and can ensure high capacity. Therefore, the Ni content is increased in the lithium transition metal composite oxide of this disclosure. On the other hand, the lithium transition metal composite oxide of this disclosure does not contain Co, or the proportion of Co in the metal elements other than Li is limited to less than 1.5 atomic%. Hereinafter, the lithium transition metal composite oxide of this disclosure will also be referred to as "composite oxide NMA".
[0019] The proportions of Ni, Mn, and Al in the composite oxide NMA, excluding Li, are as follows: Ni > 50 atomic%; Mn < 10 atomic%; and Al < 10 atomic%; and the composite oxide NMA contains no Co, or the proportion of Co in the composite oxide NMA, excluding Li, is less than 1.5 atomic%.
[0020] Mn and Al contribute to the stabilization of the crystal structure of composite oxide NMA with reduced Co content. However, the Co content of composite oxide NMA is limited to below 1.5 atomic%, and the Ni content is high, making the crystal structure prone to instability and potentially leading to the dissolution of metals such as Al and Ni. When metals dissolve, the positive electrode capacity decreases, and the cycle characteristics (or capacity retention) deteriorate. Particularly in composite oxide NMA with high Ni content, the dissolved Ni forms an oxide coating on the particle surface that hinders the absorption and release of Li ions, sometimes resulting in increased internal resistance. Furthermore, the dissolved metals can precipitate at the negative electrode, sometimes affecting the durability of the battery as a secondary battery.
[0021] In view of the above, this disclosure uses a composite oxide NMA and a non-aqueous electrolyte containing fluorosulfonate. It is believed that the anions generated by fluorosulfonate form a robust coating with Al on the particle surface of the composite oxide NMA, effectively inhibiting metal dissolution. Therefore, excellent cycling characteristics are ensured, and the increase in internal resistance during repeated charge-discharge cycles is suppressed. It should be noted that the coating derived from fluorosulfonate is presumably robust due to its excellent ionic conductivity, and therefore has minimal impact on hindering electrode reactions.
[0022] The non-aqueous electrolyte may also contain an isocyanurate component having at least one unsaturated organic group with an unsaturated carbon-carbon bond. The isocyanurate component forms a coating on the particle surface of the NMA composite oxide that suppresses side reactions. This ensures superior cycling characteristics and further suppresses the increase in internal resistance. However, when the isocyanurate component is used alone, it can sometimes form an excessively thick coating, increasing the resistance to ion conduction. In contrast, coatings derived from a combination of fluorosulfonate and isocyanurate components exhibit excellent ion conductivity. That is, fluorosulfonate also improves the ion conductivity of coatings derived from isocyanurate components.
[0023] However, even when fluorosulfonates are combined with lithium transition metal composite oxides (NMA) containing a higher Co content than NMA composite oxides, significant improvements in cycle performance and suppression of internal resistance increases are not achieved. Fluorosulfonates, however, exhibit a significant effect when combined with NMA composite oxides. This is attributed to the fact that NMA composite oxides have higher resistivity and are more brittle compared to NMA composite oxides with higher Co content. NMA composite oxide particles are prone to cracking, leading to significant metal dissolution and a noticeable increase in resistance during charge and discharge. Therefore, the improvement in properties derived from fluorosulfonate coatings is greater in NMA composite oxides. On the other hand, NMA composite oxides with higher Co content are superior under these circumstances, thus reducing the necessity of using fluorosulfonates.
[0024] The non-aqueous electrolyte secondary battery of this disclosure will be described in detail below based on its constituent elements.
[0025] [positive electrode]
[0026] The positive electrode contains a positive electrode active material. The positive electrode typically comprises a positive current collector and a layered positive electrode additive (hereinafter referred to as the positive electrode additive layer) held on the positive current collector. The positive electrode additive layer is formed by coating a positive electrode slurry, which is made by dispersing the components of the positive electrode additive in a dispersion medium, onto the surface of the positive current collector and allowing it to dry. The dried coating film can also be calendered as needed.
[0027] The positive electrode mixture contains positive electrode active material as an essential component, and can include binders, thickeners, conductive agents, etc. as optional components.
[0028] (Positive electrode active material)
[0029] The positive electrode active material comprises a composite oxide (NMA). The composite oxide NMA contains Ni, Mn, and Al, and may contain trace amounts of Co, or may not contain Co. From the viewpoint of reducing manufacturing costs, the lower the Co content, the better. The proportion of Co in the metal elements other than Li is 1.5 atomic% or less, preferably 1.0 atomic% or less, more preferably 0.5 atomic% or less, and most preferably Co-free. On the other hand, from the viewpoint of high capacity, in the composite oxide NMA, the proportions of Ni, Mn, and Al in the metal elements other than Li are: Ni 50 atomic% or more, Mn 10 atomic% or less, and Al 10 atomic% or less, respectively. The Ni content in the metal elements other than Li is preferably 80 atomic% or more, more preferably 90 atomic% or more, and may also be 92 atomic% or more. The Mn content may be 7 atomic% or less, 5 atomic% or less, or 3 atomic% or less. The Al content may be 9 atomic% or less, 7 atomic% or less, or 5 atomic% or less. Composite oxide NMA, for example, has a layered crystal structure (e.g., a rock salt-type crystal structure).
[0030] Composite oxide NMA, for example, is made from Li α Ni (1-x1-x2-y-z) Co x1 Mn x2 Al y M z O 2+β It indicates that element M is an element other than Li, Ni, Mn, Al, Co, and oxygen.
[0031] In the above formula, α, representing the atomic ratio of lithium, is, for example, 0.95 ≤ α ≤ 1.05. α increases or decreases through charging and discharging. In (2+β), representing the atomic ratio of oxygen, β satisfies -0.05 ≤ β ≤ 0.05.
[0032] The atomic ratio of Ni, 1-x1-x2-yz (=v), can be 0.5 or higher, 0.8 or higher, 0.90 or higher, or 0.92 or higher. Conversely, v can be 0.95 or lower. V can be 0.5 or higher and 0.95 or lower (0.5 ≤ v ≤ 0.95), 0.80 or higher and 0.95 or lower, 0.90 or higher and 0.95 or lower, or 0.92 or higher and 0.95 or lower.
[0033] A higher Ni atomic ratio (v) allows for the extraction of more lithium ions from the NMA composite oxide during charging, thus increasing capacity. However, this increased capacity in the NMA composite oxide tends to result in a higher Ni valence. Furthermore, a higher Ni atomic ratio leads to a relatively lower atomic ratio for other elements. In this case, especially under full charge, the crystal structure tends to become unstable, and repeated charge-discharge cycles can cause it to become inactive due to the difficulty in reversibly storing and releasing lithium ions. Consequently, cycle performance tends to deteriorate. In the non-aqueous electrolyte secondary battery disclosed in this invention, although a high Ni-content NMA composite oxide is used, excellent cycle performance is ensured by using a non-aqueous electrolyte containing fluorosulfonic acid.
[0034] The x1 representing the atomic ratio of Co is, for example, 0.015 or less (0 ≤ x1 ≤ 0.015), which can be 0.01 or less, or 0.005 or less. The case where x1 is 0 includes cases where Co is below the detection limit.
[0035] The x2, representing the atomic ratio of Mn, is, for example, less than 0.1 (0 < x2 ≤ 0.1), less than 0.07, less than 0.05, or less than 0.03. x2 can be greater than 0.01 or greater than 0.02. Mn contributes to the stabilization of the crystal structure of the composite oxide NMA, and the presence of inexpensive Mn in the composite oxide NMA helps reduce costs.
[0036] The atomic ratio of Al, y, is for example 0.1 or less (0 < y ≤ 0.1), and can be 0.09 or less, 0.07 or less, or 0.05 or less. y can be 0.01 or more, or 0.02 or more. Al contributes to the stabilization of the crystal structure of the composite oxide NMA. Furthermore, it is preferable to satisfy 0.05 ≤ x² + y ≤ 0.1. In this case, the effects of fluorosulfonate and the effect of suppressing the increase in internal resistance after repeated charge-discharge cycles are further manifested.
[0037] The atomic ratio of element M can be expressed as z, for example, 0 ≤ z ≤ 0.10, 0 < z ≤ 0.05, or 0.001 ≤ z ≤ 0.005.
[0038] Element M can be at least one selected from the group consisting of Ti, Zr, Nb, Mo, W, Fe, Zn, B, Si, Mg, Ca, Sr, Sc, and Y. Specifically, when the composite oxide MNA contains at least one element selected from the group consisting of Nb, Sr, and Ca, it is believed that the surface structure of the composite oxide NMA is stabilized, the electrical resistance is reduced, and the dissolution of metals is further suppressed. The effect is even better if element M is non-uniformly present near the particle surface of the composite oxide NMA.
[0039] The content of elements constituting the composite oxide NMA can be determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES), electron probe microanalysis (EPMA), or energy dispersive X-ray spectroscopy (EDX).
[0040] Composite oxide NMA is, for example, a secondary particle composed of multiple primary particles aggregated together. The particle size of the primary particles is generally 0.05 μm or more and 1 μm or less. The average particle size of the secondary particles of the composite oxide is, for example, 3 μm or more and 30 μm or less, or 5 μm or more and 25 μm or less.
[0041] It should be noted that, in this specification, the average particle size of secondary particles refers to the particle size that accounts for 50% of the total volume in the particle size distribution determined by laser diffraction scattering (volume average particle size). Such a particle size is sometimes referred to as D50. The measuring apparatus, for example, can be the "LA-750" manufactured by Horiba Corporation.
[0042] The composite oxide NMA can be obtained, for example, through the following steps. First, under stirring, a solution containing an alkali such as sodium hydroxide is added dropwise to a solution containing a salt of the metal element constituting the composite oxide NMA, adjusting the pH to the alkaline side (e.g., 8.5–12.5), thereby precipitating a composite hydroxide containing the metal element (Ni, Mn, Al, and, if necessary, Co, and if necessary, element M). Next, the composite hydroxide is calcined to obtain a composite oxide containing the metal element (hereinafter also referred to as "raw material composite oxide"). The calcination temperature is not particularly limited at this stage, but is, for example, 300°C–600°C.
[0043] Next, the raw material composite oxide, lithium compound, and compound containing element M as needed are mixed, and the mixture is calcined under an oxygen flow to obtain the composite oxide NMA. There are no particular restrictions on the calcination temperature at this stage; for example, it can be above 450°C and below 800°C. The calcination can be carried out in one stage, in multiple stages, or simultaneously with the heating process.
[0044] When the raw material composite oxide is mixed with lithium compound, by mixing a compound containing element M, element M can be made to exist unevenly near the particle surface of composite oxide NMA.
[0045] Lithium compounds such as lithium oxide, lithium hydroxide, lithium carbonate, lithium halides, and lithium hydrates can be used.
[0046] The positive electrode active material may contain lithium transition metal composite oxides other than NMA composite oxides, but a higher proportion of NMA composite oxides is preferred. The proportion of NMA composite oxides in the positive electrode active material is, for example, 90% by mass or more, or 95% by mass or more. The proportion of composite oxides in the positive electrode active material is 100% by mass or less.
[0047] (other)
[0048] As an adhesive, resin materials may be used, for example. Examples of adhesives include fluoropolymers, polyolefin resins, polyamide resins, polyimide resins, acrylic resins, vinyl resins, and rubber-like materials (such as styrene-butadiene copolymer (SBR)). One type of adhesive may be used alone, or two or more may be used in combination.
[0049] Examples of thickeners include cellulose derivatives such as cellulose ethers. Examples of cellulose derivatives include carboxymethyl cellulose (CMC) and its modified forms, methyl cellulose, etc. Thickeners can be used alone or in combination of two or more.
[0050] Examples of conductive agents include conductive fibers and conductive particles. Examples of conductive fibers include carbon fibers, carbon nanotubes, and metal fibers. Examples of conductive particles include conductive carbon (carbon black, graphite, etc.) and metal powders. A single conductive agent can be used, or two or more can be used in combination.
[0051] There are no particular limitations on the dispersion medium used in positive electrode slurries; examples include water, alcohols, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.
[0052] For example, metal foil can be used as the positive current collector. The positive current collector can be porous. Examples of porous current collectors include mesh, perforated sheets, and expanded metal. Examples of materials used for the positive current collector include stainless steel, aluminum, aluminum alloy, and titanium. The thickness of the positive current collector is not particularly limited, and can be, for example, 1–50 μm, or 5–30 μm.
[0053] [negative electrode]
[0054] The negative electrode contains a negative electrode active material. The negative electrode typically comprises a negative electrode current collector and a layered negative electrode additive (hereinafter referred to as the negative electrode additive layer) held on the negative electrode current collector. The negative electrode additive layer is formed by coating a negative electrode slurry, which is made by dispersing the components of the negative electrode additive in a dispersion medium, onto the surface of the negative electrode current collector and then drying it. The dried coating film can also be calendered as needed.
[0055] The negative electrode mixture contains negative electrode active material as an essential component, and can include binders, thickeners, conductive agents, etc. as optional components.
[0056] (Negative electrode active material)
[0057] As the negative electrode active material, metallic lithium, lithium alloys, etc., can be used, but materials capable of electrochemically absorbing, storing, and releasing lithium ions are preferred. Examples of such materials include carbonaceous materials and Si-containing materials. The negative electrode may contain one type of negative electrode active material, or it may contain a combination of two or more types.
[0058] Examples of carbonaceous materials include graphite, easily graphitized carbon (soft carbon), and difficult-to-graphitize carbon (hard carbon). A single carbonaceous material can be used alone, or two or more can be used in combination.
[0059] From the perspective of excellent charge-discharge stability and low irreversible capacity, graphite is the preferred carbonaceous material. Examples of graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles.
[0060] Examples of Si-containing materials include elemental Si, silicon alloys, silicon compounds (such as silicon oxides), and composite materials in which a silicon phase is dispersed within a lithium-ion conductive phase (matrix). Examples of silicon oxides include SiO₂. x Particles. x can be, for example, 0.5 ≤ x < 2, or 0.8 ≤ x ≤ 1.6. As the lithium-ion conducting phase, at least one can be selected from the group consisting of SiO2 phase, silicate phase and carbon phase.
[0061] As a binder, thickener, and conductive agent, as well as a dispersion medium used in negative electrode slurries, the material exemplified by the positive electrode can be used, for example.
[0062] Metal foil can be used as the negative current collector, for example. The negative current collector can also be porous. Examples of materials used for the negative current collector include stainless steel, nickel, nickel alloys, copper, and copper alloys. The thickness of the negative current collector is not particularly limited; for example, it can be 1–50 μm, or 5–30 μm.
[0063] [Non-aqueous electrolytes]
[0064] Non-aqueous electrolytes typically contain non-aqueous solvents and lithium salts.
[0065] (Fluorosulfonate)
[0066] Non-aqueous electrolytes include fluorosulfonates as shown in formula (1).
[0067]
[0068] In equation (1), X is a cation.
[0069] Fluorosulfonates can be at least one selected from the group consisting of FSO3Li (lithium fluorosulfonate) and FSO3Na (sodium fluorosulfonate). FSO3Li (lithium fluorosulfonate) is preferred as a lithium salt. It should be noted that fluorosulfonates can generate fluorosulfonic acid anions in non-aqueous electrolytes. Therefore, fluorosulfonic acid anions are referred to as fluorosulfonates.
[0070] The content of fluorosulfonate in the non-aqueous electrolyte can be less than 3% by mass, less than 1.5% by mass, less than 1% by mass, or less than 0.5% by mass. Within these ranges, the fluorosulfonate content can suppress excessive film formation on the positive electrode surface and improve the effect of suppressing the increase in internal resistance during repeated charge-discharge cycles. In non-aqueous electrolyte secondary batteries, the fluorosulfonate content in the non-aqueous electrolyte changes during storage or charge-discharge cycles. Therefore, it is acceptable as long as the residual fluorosulfonate in the non-aqueous electrolyte collected from the non-aqueous electrolyte secondary battery is at a concentration above the detection limit. The fluorosulfonate content in the non-aqueous electrolyte can be 0.01% by mass or more.
[0071] The content of fluorosulfonate in the non-aqueous electrolyte used in the manufacture of non-aqueous electrolyte secondary batteries can be 0.01% by mass or more, or 0.1% by mass or more, or 0.3% by mass or more. The content of fluorosulfonate in the non-aqueous electrolyte used in the manufacture of non-aqueous electrolyte secondary batteries can be, for example, 1.5% by mass or less, or 1% by mass or less, or 0.5% by mass or less. These lower and upper limits can be combined arbitrarily.
[0072] (Isocyanurate component)
[0073] The non-aqueous electrolyte may also include an isocyanurate component having at least one unsaturated organic group with an unsaturated carbon-carbon bond. The unsaturated organic group is, for example, bonded to at least one of the three nitrogen atoms constituting the isocyanuric acid ring. The isocyanurate component may have two or three nitrogen atoms of the three nitrogen atoms constituting the isocyanuric acid ring in the aforementioned unsaturated organic group.
[0074] Examples of isocyanurate components are shown in formula (2).
[0075]
[0076] Among them, R1 ~R 3 Represented by hydrogen atoms, halogen atoms, or organic groups, R 1 ~R 3 At least one of them is an unsaturated organic group having an unsaturated carbon-carbon bond. R 1 ~R 3 At least two of them can be the same, or all of them can be different.
[0077] As R 1 ~R 3 Examples of halogen atoms shown include fluorine, chlorine, bromine, or iodine atoms. Examples of organic groups include those with 1 to 20 carbon atoms. Examples of organic groups that can have substituents include hydrocarbon groups, alkoxy groups, alkoxycarbonyl groups, acyl groups, and nitrile groups. Alkoxy groups, such as R... a As shown in -O-, alkoxycarbonyl groups are as follows: R a As shown in -OC(=O)-, the acyl group is represented by R. a As shown in -C(=O)-. Among these groups, R a It is a hydrocarbon group that can have substituents.
[0078] R 1 ~R 3 and R a The hydrocarbon group shown can be any of aliphatic, alicyclic, and aromatic hydrocarbon groups. Examples of aliphatic hydrocarbon groups include alkyl, alkenyl, alkynyl, and dienyl groups. Aliphatic hydrocarbon groups can be either straight-chain or branched. The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 1 to 20, 1 to 10, 1 to 6, or 1 to 4. Examples of alicyclic hydrocarbon groups include cycloalkyl, cycloalkenyl, and cycloalkadienyl groups. The number of carbon atoms in the alicyclic hydrocarbon group is, for example, 4 to 20, 5 to 10, 5 to 8, or 5 to 6. Alicyclic hydrocarbon groups also include fused rings formed by the fusion of aromatic rings such as benzene and pyridine. Examples of aromatic hydrocarbon groups include aryl groups. Examples of aryl groups include phenyl, naphthyl, and biphenyl groups. The number of carbon atoms in the aromatic hydrocarbon group is, for example, 6 to 20, 6 to 14, or 6 to 10. Aromatic hydrocarbon groups also include fused rings formed by the fusion of non-aromatic hydrocarbon rings or non-aromatic heterocycles. The hydrocarbon rings or heterocycles can be 4-membered or 8-membered, 5-membered or 8-membered, or 5-membered or 6-membered.
[0079] Examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, hexyl, 2-ethylhexyl, decyl, tetradecyl, and stearyl. Examples of alkenyl groups include vinyl, allyl, prop-2-en-1-yl, 4-hexenyl, and 5-hexenyl. Examples of alkynyl groups include ethynyl and propynyl. Examples of dienyl groups include 1,3-butadien-1-yl. Examples of cycloalkyl groups include cyclopentyl, cyclohexyl, and cyclooctyl. Examples of cycloalkenyl groups include cyclohexenyl and cyclooctenyl. Examples of cycloalkyldienyl groups include cyclopentadienyl.
[0080] Examples of substituents that can be present in a hydrocarbon group include halogen atoms, hydroxyl groups, alkyl groups, alkenyl groups, dienyl groups, aryl groups, aralkyl groups, alkoxy groups, alkoxycarbonyl groups, acyl groups, acyloxy groups, nitrile groups, and oxygen groups (=O). Examples of halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. The number of carbon atoms in alkyl and alkoxy groups is, for example, 1 to 6, or 1 to 4. The number of carbon atoms in alkenyl, alkoxycarbonyl, acyl, and acyloxy groups is, for example, 2 to 6, or 2 to 4. The number of carbon atoms in dienyl groups is, for example, 4 to 8. Examples of aryl groups include phenyl groups with 6 to 10 carbon atoms. Examples of aralkyl groups include benzyl and phenethyl groups with 7 to 12 carbon atoms. The hydrocarbon group may have one or more of these substituents. When the hydrocarbon group has two or more substituents, at least two substituents may be the same, or all substituents may be different.
[0081] The aforementioned unsaturated organic groups only require an unsaturated carbon-carbon bond. Examples of unsaturated carbon-carbon bonds include carbon-carbon double bonds and carbon-carbon triple bonds. Among the organic groups exemplified above, examples of unsaturated organic groups include alkenyl, alkynyl, dienyl, cycloalkenyl, cycloalkadienyl, and aryl groups. From the viewpoint of excellent coating formation at the cathode, alkenyl, alkynyl, and aryl groups are preferred, with alkenyl and alkynyl groups being more preferred. Among alkenyl groups, vinyl and allyl groups are preferred. Among alkynyl groups, propynyl is preferred. It should be noted that alkenyl, alkynyl, and aryl groups also include those having the aforementioned substituents. Examples of substituents that can be present on alkenyl and alkynyl groups include halogen atoms, hydroxyl groups, aryl groups, aralkyl groups, alkoxy groups, alkoxycarbonyl groups, acyl groups, acyloxy groups, and nitrile groups. Preferably, the isocyanurate component has two or three groups selected from the group consisting of alkenyl and alkynyl groups, and more preferably, triallyl isocyanurate and diallyl isocyanurate. Triallyl isocyanurate (TIC) and diallyl isocyanurate (DIC) are shown in the following formulas, respectively.
[0082]
[0083] The isocyanurate content in the non-aqueous electrolyte is preferably 1.5% by mass or less, but can also be 1% by mass or less or 0.5% by mass or less. With an isocyanurate content within this range, excessive film formation on the positive electrode surface can be suppressed, and the effect of suppressing the increase in internal resistance during repeated charge-discharge cycles can be improved. The isocyanurate content in the non-aqueous electrolyte of the secondary battery changes during storage or charge-discharge cycles. Therefore, it is acceptable as long as the isocyanurate content in the non-aqueous electrolyte taken from the secondary battery remains at a concentration above the detection limit. The isocyanurate content in the non-aqueous electrolyte can be 0.01% by mass or more.
[0084] The isocyanurate content in the non-aqueous electrolyte used in the manufacture of non-aqueous electrolyte secondary batteries can be 0.01% by mass or more, or 0.1% by mass or more, or 0.3% by mass or more. The isocyanurate content in the non-aqueous electrolyte used in the manufacture of non-aqueous electrolyte secondary batteries can be, for example, 1.5% by mass or less, or 1% by mass or less, or 0.5% by mass or less. These lower and upper limits can be combined arbitrarily.
[0085] The content of fluorosulfonate and isocyanurate components in non-aqueous electrolytes can be determined, for example, by gas chromatography under the following conditions.
[0086] Machine used: GC-2010Plus manufactured by Shimadzu Corporation.
[0087] Column: J&W Corporation, HP-1 (film thickness 1μm, inner diameter 0.32mm, length 60m)
[0088] Column temperature: Increase the temperature from 50°C to 90°C at a rate of 5°C / min, maintain at 90°C for 15 minutes, then increase the temperature from 90°C to 250°C at a rate of 10°C / min, and maintain at 250°C for 15 minutes.
[0089] Flow split ratio: 1 / 50
[0090] Linear velocity: 30.0 cm / s
[0091] Inlet temperature: 270℃
[0092] Injection volume: 1μL
[0093] Detector: FID 290℃ (sens.10) 1 )
[0094] In the non-aqueous electrolyte, the mass ratio of isocyanurate to fluorosulfonate (=isocyanurate / fluorosulfonate) is preferably 0.5 to 1.5, and may also be 0.8 to 1.2. When the mass ratio of the two components is within such a range, the balance of the coating composition formed on the particle surface of the composite oxide NMA is improved. That is, a coating with excellent ion conductivity, a strong effect on inhibiting metal dissolution, and a strong effect on inhibiting the increase of internal resistance during repeated charge and discharge is formed.
[0095] (Non-aqueous solvent)
[0096] Examples of non-aqueous solvents include cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, and chain carboxylic acid esters. Examples of cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of cyclic carboxylic acid esters include γ-butyrolactone (GBL) and γ-valerolactone (GVL). Examples of chain carboxylic acid esters include methyl formate, ethyl formate, propyl formate, methyl acetate (MA), ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. A non-aqueous electrolyte may contain one non-aqueous solvent or a combination of two or more.
[0097] (Lithium salt)
[0098] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, and LiB. 10 Cl 10 Examples of borates include lower aliphatic carboxylic acids such as lithium, LiCl, LiBr, LiI, borates, and imide salts. Examples of borates include lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium bis(1,2-phenylene glycolate (2-)-O,O')borate, lithium bis(2,3-naphthalene glycolate (2-)-O,O')borate, lithium bis(2,2'-biphenylene glycolate (2-)-O,O')borate, and lithium bis(5-fluoro-2-olate-1-benzenesulfonic acid-O,O')borate. Examples of lithium bis(fluorosulfonyl)imide (LiN(FSO2)2), lithium bis(trifluoromethanesulfonate)imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), and lithium bis(pentafluoroethanesulfonate)imide (LiN(C2F5SO2)2). Non-aqueous electrolytes may contain one lithium salt or a combination of two or more.
[0099] The concentration of lithium salts (or lithium salts other than lithium fluorosulfonate if the fluorosulfonate is lithium fluorosulfonate) in the non-aqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less.
[0100] The non-aqueous electrolyte may contain other additives. These other additives are referred to as the second component. Examples of the second component include at least one selected from the group consisting of vinylene carbonate, fluoroethylene carbonate, and vinylene carbonate.
[0101] [Separator]
[0102] Preferably, a separator is sandwiched between the positive and negative electrodes. The separator has high ion permeability, moderate mechanical strength, and insulation properties. Microporous membranes, woven fabrics, non-woven fabrics, etc., can be used as separators. Polyolefins such as polypropylene and polyethylene are preferred as materials for the separator.
[0103] As an example of the structure of a non-aqueous electrolyte secondary battery, one can exemplify a structure in which an electrode assembly consisting of a positive and a negative electrode wound together with a separator is housed within a casing along with the non-aqueous electrolyte. However, this is not a limitation, and other forms of electrode assemblies can also be applied. For example, a stacked electrode assembly consisting of a positive and a negative electrode layered together with a separator can also be used. The shape of the non-aqueous electrolyte secondary battery is also not limited; for example, it can be cylindrical, square, coin-shaped, button-shaped, laminated, etc.
[0104] The following is for reference Figure 1 The structure of a square non-aqueous electrolyte secondary battery, which is an example of the non-aqueous electrolyte secondary battery of the present invention, will be described.
[0105] The battery comprises a square-shaped battery casing 4, an electrode assembly 1 housed within the battery casing 4, and a non-aqueous electrolyte (not shown). The electrode assembly 1 has a strip-shaped negative electrode, a strip-shaped positive electrode, and a separator sandwiched between them. The negative electrode current collector is electrically connected to a negative terminal 6 provided on a sealing plate 5 via a negative electrode lead 3. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. The positive electrode current collector is electrically connected to the back of the sealing plate 5 via a positive electrode lead 2. That is, the positive electrode is electrically connected to the battery casing 4, which also serves as the positive terminal. The periphery of the sealing plate 5 fits into the open end of the battery casing 4, and the fitting part is laser-welded. The sealing plate 5 has an injection hole for the non-aqueous electrolyte, which is plugged using a sealing plug 8 after electrolyte injection.
[0106] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited to the following embodiments.
[0107] [Example]
[0108] Examples 1-4 and Comparative Examples 1-5
[0109] Construct and evaluate non-aqueous electrolyte secondary batteries in the following order.
[0110] (1) Production of the positive electrode
[0111] 2.5 parts by weight of acetylene black, 2.5 parts by weight of polyvinylidene fluoride, and an appropriate amount of NMP were added to 95 parts by weight of positive electrode active material particles and mixed to obtain a positive electrode slurry. Next, the positive electrode slurry was coated onto the surface of aluminum foil. After the coating dried, it was calendered to coat both sides of the aluminum foil with a positive electrode additive layer (95 μm thick, 3.6 g / cm³). 3 ), thus obtaining the positive electrode.
[0112] The positive electrode active material particles are manufactured in the following order.
[0113] Prepare an aqueous solution containing dissolved nickel sulfate, aluminum sulfate, and, if necessary, cobalt sulfate or manganese sulfate. Set the concentration of nickel sulfate in the aqueous solution to 1 mol / L. For the concentrations of other sulfates, adjust the ratio of Ni to each metal element as shown in Table 1.
[0114] At 50°C, a 30% (w / w) aqueous solution containing sodium hydroxide was added dropwise while stirring the aqueous solution until the pH of the mixture reached 12, causing the hydroxide to precipitate. The hydroxide was recovered by filtration, washed with water, and dried. The dried product was calcined at 500°C for 8 hours under a nitrogen atmosphere to obtain a composite oxide.
[0115] The obtained composite oxide, lithium hydroxide, and an oxide containing element M (specifically niobium oxide or strontium oxide) were mixed in an atomic ratio of Li, total of Ni, Co, Mn, and Al, to element M of 1:1:z (specifically, the z values shown in Table 1). The mixture was calcined in an oxygen atmosphere in an electric furnace at a heating rate of 2.0 °C / min from room temperature to 650 °C. Subsequently, it was calcined again at a heating rate of 0.5 °C / min from 650 °C to 715 °C. The calcined product was washed with water and dried to obtain the composite oxide NMA (positive electrode active material particles).
[0116] (2) Fabrication of the negative electrode
[0117] Silicon composite material and graphite were mixed at a mass ratio of 5:95 and used as the negative electrode active material. The negative electrode active material, sodium salt of CMC (CMC-Na), SBR, and water were mixed at a specified mass ratio to prepare a negative electrode slurry. Next, the negative electrode slurry was coated onto the surface of a copper foil, which served as the negative electrode current collector. After the coating dried, it was calendered to form a negative electrode composite layer on both sides of the copper foil.
[0118] (3) Preparation of non-aqueous electrolytes
[0119] A non-aqueous electrolyte was prepared by dissolving LiPF6 in a mixed solvent of EC and EMC (EC:EMC = 3:7 (volume ratio), and adding fluorosulfonate (component 1) and isocyanurate (component 2) as needed, as shown in Table 1. The concentration of LiPF6 in the electrolyte was set to 1.0 mol / L. The concentrations (initial concentrations) of components 1 and 2 in the prepared non-aqueous electrolyte were set to the values (mass %) shown in Table 1.
[0120] (4) Fabrication of non-aqueous electrolyte secondary batteries
[0121] An Al-made positive electrode lead is attached to the obtained positive electrode, and a Ni-made negative electrode lead is attached to the obtained negative electrode. In an inert gas atmosphere, the positive and negative electrodes are wound into a spiral shape, sandwiched between a polyethylene film (separator), to create a wound electrode assembly. The electrode assembly is then housed in a bag-shaped outer casing formed of a laminate with an Al layer. After injecting the aforementioned non-aqueous electrolyte, the casing is sealed to create a non-aqueous electrolyte secondary battery. It should be noted that when the electrode assembly is housed in the casing, portions of the positive and negative electrode leads are exposed to the outside of the casing.
[0122] (5) Evaluation
[0123] The non-aqueous electrolyte secondary batteries obtained in the examples and comparative examples were evaluated as follows.
[0124] (a) Initial DC resistance value (DCIR)
[0125] At a temperature of 25°C, the battery was charged at a constant current of 0.3 It until the voltage reached 4.1V. Then, it was charged at a constant voltage of 4.1V until the current reached 0.05 It. Next, it was discharged at a constant current of 0.3 It for 100 minutes to bring the State of Charge (SOC) to 50%.
[0126] For a battery with a state of charge (SOC) of 50%, the voltage values were measured after discharging at currents of 0A, 0.1A, 0.5A, and 1.0A for 10 seconds. The DCIR (initial DCIR) was calculated by taking the absolute value of the slope of the relationship between the discharge current and the voltage value after 10 seconds, approximating it as a straight line using the least squares method.
[0127] (b) Charge-discharge cycle test
[0128] At an ambient temperature of 45°C, the battery was charged with a constant current of 0.5 It until the voltage reached 4.1V. Then, it was charged with a constant voltage of 4.1V until the current reached 0.02 It. Next, it was discharged with a constant current of 0.5 It until the voltage reached 3.0V. This charge-discharge cycle was defined as one cycle, and repeated 100 times.
[0129] (c) DCIR rise rate (ΔDCIR)
[0130] Except for the battery used in the charge-discharge cycle test described in (b) above, the DCIR (DCIR of the 100th cycle) is calculated in the same manner as in (a) above. The ratio of the DCIR after 100 cycles to the initial DCIR is taken as the DCIR rise rate and calculated using the following formula.
[0131] DCIR rise rate (%) = {(DCIR in the 100th cycle - Initial DCIR)} / Initial DCIR × 100
[0132] (d) Capacity retention rate (MR)
[0133] In the charge-discharge cycle test described in (b) above, the discharge capacity of the first cycle and the discharge capacity of the 100th cycle are measured, and the capacity retention rate is calculated using the following formula as an indicator of cycle characteristics.
[0134] Capacity retention (%) = (Discharge capacity at 100th cycle / Discharge capacity at 1st cycle) × 100
[0135] The evaluation results are shown in Table 1. In Table 1, E1 to E4 are Examples 1 to 4, and C1 to C5 are Comparative Examples 1 to 5.
[0136] [Table 1]
[0137]
[0138] First, a comparison between C1 and C4 shows that when using the Co-free composite oxide NMA (C1) compared to the case of using the composite oxide containing a relatively large amount of Co (C4), the capacity retention rate (MR) decreased by 2.1% (85.5% → 83.4%), while the DCIR increase rate (ΔDCIR) increased significantly by 4.6% (29.8% → 34.4%).
[0139] Next, a comparison between C1 and E1 shows that in E1, which uses a non-aqueous electrolyte containing the first component compared to C1, the capacity retention rate (MR) increases significantly by 5.7% (83.4% → 89.1%), while the DCIR increase rate (ΔDCIR) decreases by 16.1% (34.4% → 18.3%). Similarly, in E2–E4, the capacity retention rate (MR) increases significantly, while the DCIR increase rate (ΔDCIR) decreases significantly. Furthermore, the balance between capacity retention rate (MR) and DCIR increase rate (ΔDCIR) is excellent in E1–E4.
[0140] On the other hand, a comparison between C4 and C5 shows that when using C5, which contains a non-aqueous electrolyte with the first component relative to C4, the capacity retention rate (MR) increases by only 1.5% (85.5% → 87.0%), and the DCIR increase rate (ΔDCIR) decreases by only 4.7% (29.8% → 25.1%).
[0141] In other words, when using a Co-free composite oxide NMA, the effects of the first component are significantly enhanced by using a non-aqueous electrolyte containing the first component compared to using a composite oxide containing a relatively higher amount of Co. It should be noted that, compared to C1–C3, using elements M (Nb, Sr) increases capacity retention (MR) by 1.7%–2.5% and decreases DCIR rise rate (ΔDCIR) by 5.3%–6.2%.
[0142] Industrial availability
[0143] The non-aqueous electrolyte secondary battery disclosed herein is useful as a main power source for mobile communication devices, portable electronic devices, and the like. Furthermore, the high capacity and excellent cycle characteristics of the non-aqueous electrolyte secondary battery also make it suitable for automotive applications. However, the applications of the non-aqueous electrolyte secondary battery are not limited to these.
[0144] Although the invention has been described in conjunction with presently preferred embodiments, such disclosure should not be interpreted limitingly. Various modifications and alterations will be readily apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the appended claims should be construed as encompassing all modifications and alterations without departing from the true spirit and scope of this disclosure.
[0145] Explanation of reference numerals in the attached figures
[0146] 1: Electrode assembly; 2: Positive lead; 3: Negative lead; 4: Battery casing; 5: Sealing plate; 6: Negative terminal; 7: Gasket; 8: Seal plug.
Claims
1. A non-aqueous electrolyte secondary battery, comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode contains a positive electrode active material. The positive electrode active material comprises a lithium transition metal composite oxide containing Ni, Mn, and Al. The proportions of Ni, Mn, and Al in the lithium transition metal composite oxide, excluding Li, are as follows: Ni: 50 atomic percent or more Mn: less than 10 atomic percent, and Al: less than 10 atoms, When the lithium transition metal composite oxide contains Co, the proportion of Co in the metal elements other than Li is less than 1.5 atomic%. The non-aqueous electrolyte contains fluorosulfonate. The non-aqueous electrolyte further comprises: an isocyanurate component having at least one unsaturated organic group with an unsaturated carbon-carbon bond. In the non-aqueous electrolyte, the mass ratio of the isocyanurate component to the fluorosulfonate component is 0.5 to 1.
5. The isocyanurate component comprises at least one selected from the group consisting of triallyl isocyanurate and diallyl isocyanurate.
2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The lithium transition metal composite oxide is composed of the following formula Li α Ni (1-x1-x2-y-z) Co x1 Mn x2 Al y M z O 2+β As shown, the following conditions are met in this formula: 0.95≤α≤1.05、 0.5≤1-x1-x2-yz≤0.95、 0≤x1≤0.015、 0<x2≤0.1、 0<y≤0.1、 0≤z≤0.1, and -0.05≤β≤0.05, M is an element other than Li, Ni, Mn, Al, Co and oxygen.
3. The non-aqueous electrolyte secondary battery according to claim 2, wherein, The element M is selected from at least one element chosen from the group consisting of Ti, Zr, Nb, Mo, W, Fe, Zn, B, Si, Mg, Ca, Sr, Sc, and Y.
4. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein, The fluorosulfonate is selected from at least one of the groups consisting of FSO3Li and FSO3Na.
5. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein, The content of the fluorosulfonate in the non-aqueous electrolyte is less than 3% by mass.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2006310181A
Nonaqueous electrolytic solution, and nonaqueous electrolytic battery arranged by use thereof
JP2014194930A
Positive electrode active material for non-aqueous electrolyte secondary cell and method for manufacturing same, and non-aqueous electrolyte secondary cell
CN110392950A
Nonaqueous electrolyte and power storage device using the same
JP2018063942A
A Cathode Material for Lithium Secondary Batteries withNon-Aqueous Electrolyte, a Process for preparing theCathode Material and Lithium secondary Batterycontaining the same
KR1020070060784A
